Reducing anxiety and improving self-acceptance in children and adolescents with osteosarcoma through group drawing art therapy - Liu, Xin; Sun, Lihong; Du, Xinhui; Zhang, Chang; Zhang, Yijia; Xu, Xiaoxia (Frontiers in Psychology, 2023)
Purpose This study explored the effect of group drawing art therapy (GDAT) on anxiety and self-acceptance in children and adolescents with osteosarcoma. Methods Using a randomized experimental study design, 40 children and adolescents with osteosarcoma who were treated in our hospital from December 2021 to December 2022 were selected as the research objects, including 20 in the intervention group and 20 in the control group. The control group received routine care for osteosarcoma, while the intervention group participated in eight sessions of GDAT, twice a week, 90–100 min each, in addition to routine care for osteosarcoma. A screening for children’s anxiety disorders (SCARED) and a self-acceptance questionnaire (SAQ) were used to evaluate the patients before and after the intervention. Results After 8 weeks of GDAT, the SCARED total score in the intervention group was 11.30 ± 8.603, and that in the control group was 22.10 ± 11.534. The difference between the two groups was statistically significant (t = -3.357, P < 0.05). In the intervention group, the SAQ total score was 48.25 ± 4.204, with self-acceptance and self-evaluation factor scores of 24.40 ± 2.521 and 23.85 ± 2.434, respectively. In the control group, the SAQ total score was 42.20 ± 4.047; the self-acceptance factor score was 21.20 ± 3.350 and that of the self-evaluation factor was 21.00 ± 2.224. The differences between the two groups were statistically significant (t = 4.637, P < 0.001; t = 3.413, P < 0.05; t = 3.866, P < 0.001, respectively). Conclusion Group drawing art therapy can reduce anxiety and improve the levels of self-acceptance and self-evaluation in children and adolescents with osteosarcoma.